Indigenous, peasants and struggles for land/territory in the area of Belo Monte hydroelectric (Pa) - Marinho, José Antônio (2023)
In this work, it is addressed some points of the process of expropriation/dispossession of indigenous and peasants in the middle Xingu river, State of Pará, as a result of the installation of Belo Monte hydroelectric, as well as the articulations and struggles of these social groups for the right to return to the river from where they were expelled. Starting from the perspective that this process is a dimension of Brazilian agrarian question in the Amazon, the struggles of these social groups are understood as a movement in the sense of retaking (or, at least, reoccupying) fractions of the capitalist territory destined for energy exploitation in Xingu, seeking to rebuild unstructured ways of life and experiences. In these clashes, enhanced by the involvement of mediating agents, contradictions are thrown into the program of action of Belo Monte concessionaire company, allowing indigenous and peasants not only to return (still partial) to the middle Xingu, but also to dream with the creation of riparian territories in the main reservoir of the hydroelectric.